2021
DOI: 10.1017/s0016756821000601
|View full text |Cite
|
Sign up to set email alerts
|

Enrichment of heavy REE and Th in carbonatite-derived fenite breccia

Abstract: Enrichment of the heavy rare earth elements (HREE) in carbonatites is rare as carbonatite petrogenesis favours the light (L)REE. We describe HREE enrichment in fenitized phonolite breccia, focusing on small satellite occurrences 1–2 km from the Songwe Hill carbonatite, Malawi. Within the breccia groundmass, a HREE-bearing mineral assemblage comprises xenotime, zircon, anatase/rutile and minor huttonite/thorite, as well as fluorite and apatite. A genetic link between HREE mineralization and carbonatite empla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 55 publications
1
5
0
Order By: Relevance
“…We therefore suggest that REE fractionation could be a better explanation for the lower (La/Nd) cn ratios of fenite, particularly noting that the best mixing results came from quartz rock monazite-(Ce), which is of non-primary magmatic origin, and which might have formed from REE-fractionating fluids. This accords with the view of Broom-Fendley et al (2021a) and Broom-Fendley et al (2021b) who suggested that, subsequent to precipitation of LREE minerals in carbonatite, the more incompatible HREE are expelled in residual hydrothermal fluids, and that REE fractionation occurs in most cases of fenitisation.…”
Section: Ree Fractionation Further Investigatedsupporting
confidence: 91%
See 1 more Smart Citation
“…We therefore suggest that REE fractionation could be a better explanation for the lower (La/Nd) cn ratios of fenite, particularly noting that the best mixing results came from quartz rock monazite-(Ce), which is of non-primary magmatic origin, and which might have formed from REE-fractionating fluids. This accords with the view of Broom-Fendley et al (2021a) and Broom-Fendley et al (2021b) who suggested that, subsequent to precipitation of LREE minerals in carbonatite, the more incompatible HREE are expelled in residual hydrothermal fluids, and that REE fractionation occurs in most cases of fenitisation.…”
Section: Ree Fractionation Further Investigatedsupporting
confidence: 91%
“…These authors also linked increasing solubility of the MREE and HREE over time to fluids with falling temperature and a change from CO 2 to H 2 O dominance, which may have promoted (re)mobilisation of the MREE and HREE (Andrade et al , 1999; Broom-Fendley et al , 2013). This was possibly via a dissolution–reprecipitation process (Broom-Fendley et al , 2021a; 2021b) as evidenced by the presence of porous fluorapatite containing sub-micrometre zircon in medium-grade fenite and breccia at Kangankunde, and skeletal zircon in breccia at Chilwa Island.…”
Section: Discussionmentioning
confidence: 99%
“…The alkali metasomatic aureoles that surround alkaline-silicate and carbonatite intrusions are termed "fenite." Because fenite composition is controlled by protolith mineralogy, fluid composition, pressure, and temperature, it has potential for use as a vectoring tool during exploration (Elliott et al, 2018;Broom-Fendley et al, 2021). The extent of fenite is additionally controlled by country-rock permeability.…”
Section: Wall-rock Influences and Fenite Alteration Halosmentioning
confidence: 99%
“…The potassium enrichment in fenite can be mapped by radiometric surveys and used as a vector toward mineralization (Simandl, 2015;Simandl and Paradis, 2018). Because fenite aureoles are formed via fluid expulsion from a parental intrusion, their extent, mineralogy, and geochemistry record information about the metal tenor of the parent intrusion (Dowman et al, 2017;Broom-Fendley et al, 2021). This effect is not yet characterized to a sufficient level for widespread use in exploration.…”
Section: Wall-rock Influences and Fenite Alteration Halosmentioning
confidence: 99%
“…Elliott et al (2018) explain that the occurrence of breccias at several carbonatite complexes corroborates the explosive release of fluids and volatiles from an evolving magma underneath. For Songwe carbonatite, Broom-Fendley et al (2021) stress that based on the angular nature of the clasts and the comminuted groundmass, the breccia formed by in situ rapid volume expansion, most likely as a result of subsurface explosive release of volatiles from the proposed underlying carbonatite bodies. Thus, the explosive hydrothermal brecciation and the metasomatic action of hydrothermal fluids can indeed be considered responsible for the generation of the breccia.…”
Section: Location and Geology Of The Study Areamentioning
confidence: 99%